A bibliometric and visualization analysis of the role of traditional Chinese medicine in cancer immunotherapy - Lian, Yixiao; Sun, Jie; Yang, Lin; Yu, Weidong (Frontiers in Immunology, 2025)
ObjectiveTraditional Chinese medicine (TCM) is used as a complementary treatment for patients with cancer, especially in immunotherapy. Although extensive clinical and basic research has been conducted on TCM in cancer immunotherapy, a comprehensive bibliometric analysis of this field has not yet been performed. This study aimed to investigate the progress and status of TCM, and the research focused on cancer immunotherapy.MethodsWe collected 1,657 articles on TCM in cancer immunotherapy from 1994 to 2024 from the Web of Science Core Collection database. VOSviewer, CiteSpace, and the Bibliometrix R package were used to analyze countries, institutions, journals, authors, references, and keywords to predict future trends in cancer immunotherapy with TCM.ResultsThe publication rate of TCM in cancer immunotherapy research steadily increased from 1994 to 2018, with a swift growth from 2018 to 2023. China and TCM universities have achieved the most research advancements in this field. The most studied types of cancer are liver, lung, and colorectal cancers. However, few studies exist on upper respiratory tract tumors, cervical cancer, and melanoma, which deserve more attention. The study trend has gradually shifted from in vivo and in vitro models to clinical efficacy. Simultaneously, the focus of research transitioned from compound TCM preparations or classes of ingredients to specific pharmacodynamic ingredients, and the corresponding targets transitioned from cytokines to immune checkpoints. In general, molecular docking combined with multi-omics analysis is a popular and trending research method in TCM for cancer immunotherapy, helping researchers understand the mechanisms of TCM in cancer immunotherapy more comprehensively and accurately. By analyzing the literature, it is evident that TCM-based immunotherapy should contribute to effective maintenance or adjuvant therapy throughout the entire course of cancer rather than only in the late stages.ConclusionThis study comprehensively summarized and identified research frontiers providing a reference for promoting the development of TCM immunotherapy preparations and guiding clinical practice. Consequently, more patients with cancer can benefit from immunotherapy.